Comparison and Outcome Analysis of Patients with Takotsubo Cardiomyopathy Triggered by Emotional Stress or Physical Stress - Giannakopoulos, Konstantinos; El-Battrawy, Ibrahim; Schramm, Katja; Ansari, Uzair; Hoffmann, Ursula; Borggrefe, Martin; Akin, Ibrahim (Frontiers in Psychology, 2017)
Background: Previous studies revealed that Takotsubo cardiomyopathy (TTC) is triggered by physical and emotional stresses. This study was performed to determine the short- and long-term prognostic impact of emotional- and physical stress associated with TTC. Methods and results: Our institutional database constituted a collective of 84 patients diagnosed with TTC between 2003 and 2015. The patients were divided into two groups as per the presence of emotional stress (n=24, 21%) or physical stress (n=60, 52.6%). The endpoint was a composite of in-hospital events (thromboembolic events and life-threatening arrhythmias), myocardial infarction, all-cause of mortality, re-hospitalization due to heart failure, stroke, and recurrence of TTC. A Kaplan-Meier analysis indicated a significantly lower event-free survival rate over a mean follow-up of 5 years in the emotional group than the physical stress group (log-rank, p<0.01). Multivariate Cox regression analysis revealed only emotional stress (HR 0.4, 95% CI: 0.2-0.9, p<0.05) as a negative independent predictor of the primary endpoint. Conclusion: Rates of in-hospital events and short- as well as long-term events were significantly lower in TTC patients suffering from emotional stress as compared to patients with physical stress.